Un projet de recherche exempté d’évaluation éthique : Réflexions et questionnements sur l’article 2.1 de l’Énoncé de politique des trois Conseils - Fortin, Marie-Chantal; Durand, Céline (BioéthiqueOnline, 2012)
This case study presents the Article 2.1 of the Tri-council Policy Statement, which now allows some qualitative research with minimal risk to be exempt from ethics review. However, its application raises questions.